2015
DOI: 10.1128/iai.00180-15
|View full text |Cite
|
Sign up to set email alerts
|

Streptococcus pyogenes Triggers Activation of the Human Contact System by Streptokinase

Abstract: Severe invasive infectious diseases remain a major and life-threatening health problem. In serious cases, a systemic activation of the coagulation cascade is a critical complication that is associated with high mortality rates. We report here that streptokinase, a group A streptococcal plasminogen activator, triggers the activation of the human contact system. Activation of contact system factors at the surface of the Streptococcus pyogenes serotype M49 is dependent on streptokinase and plasminogen. Our result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 41 publications
0
28
0
Order By: Relevance
“…Three main groups of proteinases can be distinguished: (I) those that activate FXII, but not pro-pKal; (II) those that can activate both FXII and pro-pKal; and (III) those that directly liberate bradykinin from HK. Finally, recent studies have shown that bacterial strains that carry direct plasminogen activators (e.g., streptokinase) can trigger plasmin-triggered bradykinin production via the contact system (27), which is highly reminiscent of earlier studies that identified plasmin as an activating enzyme of FXII (28) as well as recent findings that implicate plasmin as FXII-activating enzyme in hereditary angioedema (HAE) (29). This may help to explain the changes in blood pressure that take place during sepsis but also possibly points toward a bradykinin-dependent mechanism of pathogen host invasion.…”
Section: The Contact System In Inflammatory Pathologymentioning
confidence: 88%
See 1 more Smart Citation
“…Three main groups of proteinases can be distinguished: (I) those that activate FXII, but not pro-pKal; (II) those that can activate both FXII and pro-pKal; and (III) those that directly liberate bradykinin from HK. Finally, recent studies have shown that bacterial strains that carry direct plasminogen activators (e.g., streptokinase) can trigger plasmin-triggered bradykinin production via the contact system (27), which is highly reminiscent of earlier studies that identified plasmin as an activating enzyme of FXII (28) as well as recent findings that implicate plasmin as FXII-activating enzyme in hereditary angioedema (HAE) (29). This may help to explain the changes in blood pressure that take place during sepsis but also possibly points toward a bradykinin-dependent mechanism of pathogen host invasion.…”
Section: The Contact System In Inflammatory Pathologymentioning
confidence: 88%
“…We recently reported that three types of FXII mutations that cause HAE enhance the capacity of plasmin to cleave and activate FXII through introduction of novel enzymatic cleavage sites, leading to uncontrolled bradykinin production despite the presence of normal C1inh levels (29). Interestingly, the plasminogen activation system is linked in many of the inflammatory conditions described above, ranging from bacterial plasminogen activators to concurrent activation of plasminogen and the contact system in anaphylaxis (27, 30, 32). Based on these combined findings, we propose that plasmin is of importance for FXII-mediated bradykinin production in a context that expands beyond HAE.…”
Section: Two External Enzymes That Feed Into the Contact System Durinmentioning
confidence: 99%
“…The accumulation of streptokinase on the surface of speB -null GAS has been proposed to be essential in the promotion of invasive illness [37]. It was previously shown that streptokinase could cleave Factor XII to active Factor XIIa [75]. In a recent publication, Wollein Woldetoft et al .…”
Section: Newly Discovered Roles For Virulence Factorsmentioning
confidence: 99%
“…4c). We therefore concluded that Δ ska supernatant generates small amounts of plasmin from its precursor, although lacking the plasminogen activator streptokinase and failing to induce plasmin activity measured by a substrate assay [18,25]. As the plasmin inhibitor cannot interfere with the streptokinase-plasminogen/plasmin complex [26], WT supernatant led to an efficient plasminogen-dependent degradation of CTH, even in the presence of the inhibitor (fig.…”
Section: Resultsmentioning
confidence: 99%